Staged multidisciplinary step‐up management for necrotizing pancreatitis. Issue 1 (22nd November 2013) - da Costa, D. W.; Boerma, D.; van Santvoort, H. C.; Horvath, K. D.; Werner, J.; Carter, C. R.; Bollen, T. L.; Gooszen, H. G.; Besselink, M. G.; Bakker, O. J.
Abstract : Background: Some 15 per cent of all patients with acute pancreatitis develop necrotizing pancreatitis, with potentially significant consequences for both patients and healthcare services . Methods: This review summarizes the latest insights into the surgical and medical management of necrotizing pancreatitis. General management strategies for the treatment of complications are discussed in relation to the stage of the disease . Results: Frequent clinical evaluation of the patient's condition remains paramount in the first 24–72 h of the disease. Liberal goal‐directed fluid resuscitation and early enteral nutrition should be provided. Urgent endoscopic retrograde cholangiopancreatography is indicated when cholangitis is suspected, but it is unclear whether this is appropriate in patients with predicted severe biliary pancreatitis without cholangitis. Antibiotic prophylaxis does not prevent infection of necrosis and antibiotics are not indicated as part of initial management. Bacteriologically confirmed infections should receive targeted antibiotics. With the more conservative approach to necrotizing pancreatitis currently advocated, fine‐needle aspiration culture of pancreatic or extrapancreatic necrosis will less often lead to a change in management and is therefore indicated less frequently. Optimal treatment of infected necrotizing pancreatitis consists of a staged multidisciplinary 'step‐up' approach. The initial step is drainage, either percutaneous or transluminal, followed by surgical or endoscopic transluminal debridement only if needed. Debridement is delayed until the acute necrotic collection has become 'walled‐off' . Conclusion: Outcome following necrotizing pancreatitis has improved substantially in recent years as a result of a shift from early surgical debridement to a staged, minimally invasive, multidisciplinary, step‐up approach . Abstract : Optimal management of a dreaded disease